On the Feasibility of Slope Stability Analysis during Freezing and Thawing - Sjöbeck, Gustav (My University, 2023)
The topic for this thesis is to investigate slope stability in relation to climate driven condition changes. Focus was directed on freeze and thaw process of soil and how it affects the stability of slopes. This is then linked to a case study close to Bispgården in Sweden. The Bispgården case had strong indications of frost related damages. The thesis further present freeze and thaw related movement and behaviors of the soil. Mainly focusing on phase change, displacements, water and ice saturation and heat distribution within in the soil body. The frozen and unfrozen soil model in PLAXIS was used to model the behavior of a freezing and thawing soil. Resulting in a analyze that indicated a reduction of the slope stability in a semi frozen stage. However, was the use of this model numerically challenging and very sensitive to parameter changes. The conclusion could be drawn that the feasibility of accurately analyzing freeze and thaw related stability problems are limited, due to the high prerequisite. Very specific data- and skill-sets are needed to utilize the potential. This could be problematic with the potential effects of the ongoing climate change in mind.
Keywords: Slope stability, freezing soil, thawing soil, phase change, frozen and unfrozen soil model